Effects of mg and la co-doping on dielectric, ferroelectric, and piezoelectric properties of barium calcium zirconate titanate ceramics - Panupong Jaiban (2020)
© 2020, Chiang Mai University. All rights reserved. In this study, the barium calcium zirconate titanate ceramics with Mg and La doping are prepared by employing a conventional solid-state sintering technique. The addition of Mg ions decreases the sintering temperature of BCZT ceramic. All ceramics show dense microstructure with different grain sizes. X-ray diffraction patterns indicate the co-existence of rhombohedral and tetragonal phases in these ceramics. Upon doping, the shift of phase transition temperature to lower temperature and a broad dielectric peak are induced. The co-doping enhances the maximum dielectric constant at high temperatures. Ferroelectric and piezoelectric properties of BCZT show a decreasing trend with the doping. The result here suggests that the fabrication, microstructure, electrical properties of BCZT ceramic can be tunable via La or Mg doping, which may be used in dielectric devices.